The Lived Experiences of SEAMEO INNOTECH GURO21 Graduates (International Journal of Theory and Application in Elementary and Secondary School Education, 2020)
This study examines the experiences of eight teachers who have graduated from an online course. The SEAMEO INNOTECH GURO21. The primary data collection method made use of one on one interviews.  The results of the study informed that in understanding the lived experiences of those who graduated from the first course of SEAMEO INNOTECH GURO21 can be categorized into two themes: (a) equipping teachers with the knowledge, skills, attitudes and values of the 21st century; and (2) facilitating 21st century learning. This research revealed that as teachers, one must be knowledgeable enough to carefully choose strategies and techniques tailored-fit for the kind and level of the learners. The acquisition of the 21st century skills has become an essential part of the generation. Thus, teachers must undergo seminars and workshops and even enroll in online courses to be upgraded with the latest trends of this generation. The participants, from their responses, revealed the change within themselves in line with their profession and in the development of their personality. The course had made them shift from being a traditional teacher to a techno-savvy one. This means using techniques and strategies the old way and how they smoothly transformed into technology-based teaching. Recommendations are offered for school heads, and for further research. This is to further enhance this study and to compare other findings in line with teacher development programs through online courses.